A free interface component mode synthesis method for viscoelastically damped systems. (17th March 2016) - Ding, Zhe; Li, Li; Hu, Yujin
Abstract: The analysis of large, complex systems can be simplified and more computationally efficient if smaller, simpler subcomponents can be treated and assembled. Component Mode Synthesis (CMS) methods allow one to reduce the order of the model at the subcomponent level. Although CMS methods are widely applied in the field of structure dynamics for undamped or viscously damped systems, their counterparts for viscoelastically damped systems seem not well-developed. Motivated by such points, this paper develops a model-order-reduction approach for viscoelastically damped systems based on a free interface CMS method. Due to the fact that the nonviscous modes and higher-order elastic modes are difficult to be obtained accurately for viscoelastic systems, the mode truncation error is often introduced. To reduce the mode truncation error problem, two residual attachment modes of viscoelastically damped systems are proposed in terms of the lower modes and system matrices by using the first one or two terms of Neumann expansion. Finally, three numerical studies are provided to illustrate the accuracy and effectiveness of the derived methods. It is shown that the proposed methods can receive good results and reduce the modal truncation error significantly over the conventional method. Abstract : Highlights: This study considers component mode synthesis for viscoelastically damped systems. Two residual modes for viscoelastically damped systems are proposed. Substructures are assembled in the physical space. The influence of modal truncation problems are reduced significantly. Three examples are provided to illustrate the accuracy and effectiveness of the proposed methods.